Verification of the neo-Marxist concept of global semi-periphery (on the example of the role of the migration factor) - Mikhailouski, Vadzim S. (Journal of the Belarusian State University. Sociology, 2021)
Neo-Marxism world-system analysis was an effective means of the understanding of the postcolonial global order. The concepts of «core», «periphery» and «semi-periphery» reflected the dependent development of states in the global capitalist system. Capitalism structured the global order in the classical Marxist dichotomy of exploiters and exploited which can be represented with various subjects (states, groups of states, territories) and which according to neo-Marxism can’t disappear, because it reflects the essence of global antagonism. However, the realities of global development at the end of the 20th century demanded that neo-Marxism should reconsider the rigid link between the core-peripheral approach and the horizontal vision of the world: globalisation caused massive flows of migrants to highly developed countries and the gradual blurring of the boundaries between the core and periphery. There was the question in neo-Marxism which was about the ability of capitalism to preserve the core-peripheral organisation of the global division of labour. There was the idea that capitalism was able to reproduce core-periphery relations within the core states by including immigrants in the super-exploitation of labour through a covert policy of neo-racism. Such a vertical organisation of the core-peripheral model around the world, which was called dual society in neo-Marxism, would mean the formation of the global semi-periphery. The purpose of the article is to verify the neo-Marxist concept of the global semi-periphery using the example of the role of the migration factor in its formation. The study is based on UN data, as well as studies with a pronounced statistical component. According to the results of the study, it was concluded that the neo-Marxist concept of the global semi-periphery had not been verified by actual empirical material (on the example of the role of the migration factor). The available statistical and analytical data do not allow to totally confirm the neo-Marxist position that the global order under the influence of migration has been transformed and that it works in the conceptual model of a dual society. Globally, migration is not a determining factor in the widespread formation and unification of the dual method of labour exploitation within states. The quantitative data on the flow of migrants, comparative data on salaries in the countries of the core and the degree of concentration of income among certain groups of the population in the countries of the capitalist system state that the world is still largely reproduced in the horizontal core-peripheral model. Thus, there are no empirical grounds for stating the presence of a global dual society under the influence of the migration factor and consequently the presence of a global semi-periphery within the neo-Marxist approach of E. Balibar, I. Wallerstein, M. Hardt and A. Negri.
Keywords: neo-Marxism; world-system analysis; global semi-periphery; migration; immigrants; global order